Automatic Program Development A Tribute to Robert Paige - Danvy, Olivier; Mairson, Harry; Henglein, Fritz; Pettorossi, Alberto; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
Automatic Program Development is a tribute to Robert Paige (1947-1999), our accomplished and respected colleague, and moreover our good friend, whose untimely passing was a loss to our academic and research community. We have collected the revised, updated versions of the papers published in his honor in the Higher-Order and Symbolic Computation Journal in the years 2003 and 2005. Among them there are two papers by Bob: (i) a retrospective view of his research lines, and (ii) a proposal for future studies in the area of the automatic program derivation. The book also includes some papers by members of the IFIP Working Group 2.1 of which Bob was an active member. All papers are related to some of the research interests of Bob and, in particular, to the transformational development of programs and their algorithmic derivation from formal specifications. Automatic Program Development offers a renewed stimulus for continuing and deepening Bob's research visions. A familiar touch is given to the book by some pictures kindly provided to us by his wife Nieba, the personal recollections of his brother Gary and some of his colleagues and friends.
Robert Paige's Research: A Retrospective and A Proposal -- Research Retrospective on Transformational Development of Programs -- A National Science Foundation Proposal -- Robert Paige: Brother, Friend, Colleague -- A Song for My Brother -- Robert Paige: Researcher and Teacher -- An Appreciation of Bob Paige -- Bob Paige and the IFIP Working Group 2.1 -- Remembrances of Bob Paige -- Contributed Papers -- Transformational Derivation of an Improved Alias Analysis Algorithm -- Dynamic Programming via Static Incrementalization -- Automatic Program Generation from Formal Specifications using APTS -- Universal Regular Path Queries -- Derivation of Efficient Logic Programs by Specialization and Reduction of Nondeterminism -- Computational Divided Differencing and Divided-Difference Arithmetics -- Least Reflexive Points of Relations -- Relativizations for the Logic-Automata Connection -- Efficient Type Matching -- Aspects as Invariants -- Program Transformations: Some Lessons from the 1980s.
Keywords: Computer science; Software engineering; Computer programming; Programming languages (Electronic computers).; Computer Science; Software Engineering/Programming and Operating Systems; Software Engineering; Programming Techniques; Programming Languages, Compilers, Interpreters; Electronic books